2020
DOI: 10.3390/agronomy10030379
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Digestate on Soil Organic Carbon and Plant-Available Nutrient Content Compared to Cattle Slurry and Mineral Fertilization

Abstract: Digestate contains many valuable nutrients, including nitrogen (N), phosphorus (P), and potassium (K); however, it is characterized by relatively little organic matter. The objective of this study was to assess the four-year impact of digestate (Dig) application, digestate + straw (Dig + St), cattle slurry (Csl), and mineral fertilization (NPK) on soil organic carbon (SOC), total nitrogen (TN), mineral N (Nmin), and the content of plant-available P and K. Fertilization did not have any significant influence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 55 publications
1
36
0
2
Order By: Relevance
“…The application of organic manures and straw represents the possible ways to add organic matter to the soil. Digestates contain many valuable nutrients, such as N, P and K [26]. As the main aim of the biogas stations is producing the biogas, consisting mainly of methane, the C content is not a strong side of the digestate when compared with compost and organic manures [81,82].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The application of organic manures and straw represents the possible ways to add organic matter to the soil. Digestates contain many valuable nutrients, such as N, P and K [26]. As the main aim of the biogas stations is producing the biogas, consisting mainly of methane, the C content is not a strong side of the digestate when compared with compost and organic manures [81,82].…”
Section: Discussionmentioning
confidence: 99%
“…Without other organic manures, or the amount of applied manures contribution of digestate is low, and the SOC content decreases significantly in the long-term period (see Section 3.3., Model 3). In comparison with organic manures, the long-term field trials have not yet shown any negative impacts of digestate on the SOC content [26,83]. The long-term effects of digestate on the environment, soil and human health have been still studied [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, a balanced use of fertilizer can increase the SOC content in the soil. In a study by Barlog et al [10], the main factor determining SOC content in different soil depths was the year. According to the year, SOC values ranged from 14.8 (2016) to 15.6 g kg −1 (2013) in topsoil (0-0.3 m), and from 7.5 (2015) to 10.4 g kg −1 (2013) in subsoil (0.3-0.6 m).The multiannual research conducted by Yang et al [11] indicated that the use of mineral fertilizer along with farmyard manure (FYM) results in a more significant increase in the amount of SOC than fertilization with mineral fertilizer only.…”
Section: Introductionmentioning
confidence: 99%